O COMPORTAMENTO INTRAEMPREENDEDOR E O DESEMPENHO HUMANO EM SERVIÇOS EDUCACIONAIS - MARIANI, JONATÃ DA SILVA (2016)
Studies focused on entrepreneurship and its consequences constantly appear in the scientific literature related to the production of innovations and competitive advantages. In turn, the intrapreneurship school brought forth the idea that the entrepreneurial behavior of people in the service of the institutions where they work is an important component of their individual skills and contributes to organizational change and to adapt the organization to the increasingly unstable environments business, resulting in competitiveness and survival factor. This study addresses the intrapreneurship a behavioral perspective founded by the vision of strategic people management and recognized as a factor that contributes to making the most dynamic organizations, flexible and intelligent. The investigation marks the analysis of intrapreneur behavior in middle management of higher education institutions (HEIs), whose positions are usually held by teachers without the necessary formal qualifications for the exercise of management, seeking the relationship between the dimensions of this behavior with the performance organizational represented by the result obtained by the courses in which they operate, according to the index used by the Ministry of Education. For it was conducted a quantitative study in IES of the same educational group with unified strategies and policies in order to measure the intrapreneur behavior of their managers, in addition to obtaining grants for the construction of individual performance indicators for its employees. The method used for the survey was used to Likert self-report questionnaire that evaluates the intrapreneur behavior in the dimensions innovation, risk taking and proactiveness. The results were statistically analyzed via specific software and the tests show that the presence of this behavior has no significant relationship with government performance indicators within the sample, suggesting that their influence rubs off on marketing aspects, such as the satisfaction of service users.